Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

So I have this fairly complicated fraction, and I am trying to find its antiderivative.

$$ \int \frac{7xe^{2x}}{(1+2x)^2} dx $$

I am not sure where to start. I was thinking using integration by parts, but then I tried substituting it with $u$'s:

$$ u = 1+2x, du = 2 dx \to dx=\frac{du}{2} \\ = \int \frac{\frac{7u-7}{2}e^{u-1}}{u^2}\color{red}{\frac{ du}{2} }\\ = \frac{7}{4}\int \frac{e^{u-1}}{u} du - \frac{7}{4}\int \frac{e^{u-1}}{u^2} du $$

But now I am stuck and I can't go any further. Can someone please guide me through this problematic integration? Thanks!

share|cite|improve this question
up vote 11 down vote accepted

$$ = \frac{7e^{-1}}{4}\bigg\{\color{red}{\int \frac{e^{u}}{u} du} - \int \frac{e^{u}}{u^2} du\bigg\}\\ = \frac{7e^{-1}}{4}\bigg\{\color{red}{\frac{e^{u}}{u}-\int \frac{-e^{u}}{u^2} du }- \int \frac{e^{u}}{u^2} du+c\bigg\}\ \text{integration by parts}\\ =\frac{7e^{-1}}{4}\frac{e^{u}}{u}+c =\frac{7e^{u-1}}{4u}+c =\frac{7e^{2x+1-1}}{4(2x+1)}+c =\frac{7e^{2x}}{4(2x+1)}+c $$

share|cite|improve this answer
Thanks for the response but I am having hard time figuring out what did you substitute for $u$. Can you explain it more? – Derek 朕會功夫 Jan 31 '14 at 5:26
i will in the answer now – Sameh Shenawy Jan 31 '14 at 5:26
i use integration by parts in the red term – Sameh Shenawy Jan 31 '14 at 5:29
$\int fg'dx=fg-\int gf'dx$ – Sameh Shenawy Jan 31 '14 at 5:31
He started from where you left the problem. So $u=2x+1$. – John Habert Jan 31 '14 at 5:32

First, let's pull out the constant factor $7$. The denominator being a square suggests trying to find functions $f(x)$, $g(x)$ such that $$\frac{d}{dx}\left[\frac{f(x)}{g(x)}\right] = \frac{f'(x)g(x) - f(x)g'(x)}{g(x)^2} = \frac{xe^{2x}}{(1+2x)^2}.$$ This in turn suggests trying $g(x) = 1+2x$, so that the numerator becomes $$(1+2x)f'(x)- 2f(x) = xe^{2x}.$$ If $f(x) = h(x) e^{2x}$ for some polynomial $h$, then $f'(x) = h'(x)e^{2x} + 2h(x) e^{2x} = (h'(x)+2h(x))e^{2x}$, hence $$xe^{2x} = (4xh(x) + (1+2x)h'(x))e^{2x}.$$ This is easily satisfied with the choice $h(x) = 1/4$, so $f(x) = e^{2x}/4$ and an antiderivative is $$7 \frac{f(x)}{g(x)} + C = \frac{7e^{2x}}{4(1+2x)} + C.$$ Of course, this method doesn't always work, but it is an interesting approach.

share|cite|improve this answer
It is interesting indeed I did not even think of ever trying this – Millardo Peacecraft Jan 31 '14 at 5:30
How did you get $xe^{2x} = (4xh(x) + (1+2x)h'(x))e^{2x}$ from the above? I was following but this line confuses me. – Derek 朕會功夫 Jan 31 '14 at 5:40
If $f(x) = h(x) e^{2x}$, then $f'(x) = (h'(x) + 2h(x))e^{2x}$, and $(1+2x)f'(x) - 2f(x) = (4xh(x) + (1+2x)h'(x))e^{2x}$, which we equate with the numerator of the integrand, assuming that it is the derivative of some quotient of functions. – heropup Jan 31 '14 at 5:43


If we choose $\displaystyle f'(x)=\frac{2A}{(1+2x)^2}, f(x)=-\frac A{1+2x}$

$$\frac{d\left[e^{2x}\cdot\frac{-A}{1+2x}\right]}{dx}=e^{2x}\left[\frac{2A}{(1+2x)^2}-2\frac A{1+2x}\right]=2Ae^{2x}\cdot \frac{1-(1+2x)}{(1+2x)^2}= \frac{-4Ax e^{2x}}{(1+2x)^2}$$

Compare with the given integral to find $-4A=7$

share|cite|improve this answer

d/dx(7*e^2/4*(2x+1))=7xe^2/x(1+2x)^2 =>d(7*e^2/4*(2x+1))=(7xe^2/x(1+2x)^2)dx Hence you get the required integral.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.